RESOR DI TENGAH KOTA DI SURAKARTA - Kartika Fitri Annisa; Agung Kumoro Wahyuwibowo; Suparno Suparno (Universitas Sebelas Maret Surakarta, 2016)
The design of Urban Resort motivated by the increasing number of tourists coming to the city of Solo as increasing tourism potential. The increasing number of tourist coming and tourist potential are not accompanied by an increase in the numbers LOS (Length Of Stay) and the availability of lodging facilities that accommodate in Solo. The purpose of this scheme is to get a building design that is able to accommodate the needs of lodging accommodations and recreation in the form of a resort hotel in the center of the city of Solo with the implementation of ecological architecture as a form of support to the Government to make Solo as an ecological city. Design issues are: how the concept of ecological architecture can be applied in the design of Urban Resort in Surakarta. The method used is the method of architectural design with mix of the theory about ecological architecture with Government Regulation about requirements of five star resort hotel. The results obtained are the design of urban resort as a means of lodging accommodations, and public space as a tourist attraction and people who apply the concept of ecology architecture on the shape and appearance of the building. So that the building can give the impression of a comfortable and natural even though the resort hotel located in the middle city of Solo.